Implementation of Problem Based Learning Model on Students' Mathematical Problem-Solving Ability - Haniva Zulfayeni; Minora Longgom Nasution; Mirna Mirna; Yulyanti Harisman (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Mathematical problem-solving ability is an essential competency that students must possess in mathematics learning. However, this ability among eleventh-grade students at SMA Pembangunan Laboratorium UNP remains suboptimal, as reflected in students' difficulties in understanding the problem, devising a strategy, carrying out the solution, and reviewing the results. Therefore, a learning model capable of actively engaging students in the problem-solving process is required, one of which is the Problem Based Learning model. This study aims to analyze whether the mathematical problem-solving ability of students taught using the PBL model is better than that of students taught using the direct instruction model. This study employed a quasi-experimental method with a Non-equivalent Posttest-Only Control Group Design, as the equivalence of the two classes' prior ability was determined based on previous mathematics scores indicating relatively comparable ability. The sample was selected through purposive sampling, namely class XI F5 as the experimental group (31 students) and class XI F6 as the control group (32 students), on the basis of their comparable ability and being taught by the same teacher. The research instrument consisted of a validated essay test of mathematical problem-solving ability with high reliability (r₁₁ = 0.80), scored using a scoring rubric. The data were analyzed using descriptive statistics and Welch's t-test, as the data did not meet the assumption of homogeneity of variance. The results showed that the mean posttest score of the experimental class (79.03) was higher than that of the control class (62.72), with a significant difference (p-value < 0.05) and a large effect size (Cohen's d = 1.15). Thus, on the topic of Circles in eleventh grade at SMA Pembangunan Laboratorium UNP, the Problem Based Learning model was better than the direct instruction model in improving students' mathematical problem-solving ability.